CONCEPTUALISING A FIDUCIARY DUTY ON AUDITORS (UUM Journal of Legal Studies, 2013)
Auditors are a key feature of a company. They perform an important role as they report on a company’s financial affairs. The report is presented at the company’s general meeting for the benefit of shareholders of the company who will consequently evaluate the performance of the company’s management. Furthermore, the report is lodged at Companies Commission of Malaysia which can be accessed by various parties who wish to rely on the report. Hence, auditors hold a public office and auditors’ report is considered as a public document. In light of this, this paper explores the possibility of attaching a fiduciary duty on auditors. This paper then proceeds to examine the manner courts deal with this concept. This is important since the concept is used extensively in relation to directors, company secretaries, receivers and liquidators. Nonetheless, in relation to auditors, it is relatively a new concept. This paper will also examine the challenges faced by auditors with this new concept. In 2007, essentially a new provision was incorporated in the Companies Act 1965 imposing a duty of good faith on auditors and to be absolved from any civil or criminal liability. Hence, this paper examines the implications of imposing such a duty on auditors. Interviews were carried out with auditors, academics, professional bodies, relevant bodies and regulatory bodies to derive in-depth views on the subject matter. Be that as it may, the duty to act in good faith is imposed on most professionals and due to the fact that auditors are professionals, the legislature imposed a similar duty on auditors. The fiduciary duty imposed on auditors will bring about more rights not only to shareholders but other parties too. Thus, this will enhance the duties and obligation of auditors in the current corporate atmosphere. This is essential as there are an increasing number of financial scandals which involve auditors. Thus, imposition of a fiduciary duty further improves the reputation of the audit profession.